2003
DOI: 10.1016/s0960-9822(03)00461-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Muscle Cell Identities Induced by Distinct Levels and Timing of Hedgehog Activity in the Zebrafish Embryo

Abstract: Hh signaling acts in a dosage-dependent manner to specify cell fate in the zebrafish myotome. Allocation of the correct number of cells to a specific fate depends upon the range of Hh activity. The timing of exposure to Hh determines the response of cells to the signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
360
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(386 citation statements)
references
References 44 publications
24
360
2
Order By: Relevance
“…Hedgehog signals for proper development: superficial slow fibers (SSFs), which migrate from the midline to populate the surface of the myotome, and slow muscle pioneers that remain close to the midline 6,8 . Muscle pioneers require higher levels of and longer exposure to Hedgehog for proper specification than SSFs and can be distinguished from slow muscle fibers by the expression of the transcription factor Engrailed (Eng) 4,6 . In situ hybridization demonstrated that inhibition of miR-214 function resulted in a loss of eng2a-positive cells during early segmentation (Fig.…”
Section: Competing Interests Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedgehog signals for proper development: superficial slow fibers (SSFs), which migrate from the midline to populate the surface of the myotome, and slow muscle pioneers that remain close to the midline 6,8 . Muscle pioneers require higher levels of and longer exposure to Hedgehog for proper specification than SSFs and can be distinguished from slow muscle fibers by the expression of the transcription factor Engrailed (Eng) 4,6 . In situ hybridization demonstrated that inhibition of miR-214 function resulted in a loss of eng2a-positive cells during early segmentation (Fig.…”
Section: Competing Interests Statementmentioning
confidence: 99%
“…Presomitic mesodermal cells immediately adjacent to the notochord (adaxial cells) are highly influenced by Hedgehog and give rise to the slow-twitch muscle lineage 5,6 . Lateral presomitic cells give rise to fast-twitch muscle fibers and experience little stimulation by Hedgehog initially, whereas later-developing fast-muscle fates are dependent on Hedgehog signaling 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Final concentrations of cyclopamine and DAPT were 15 and 100 M, respectively (Wolff et al, 2003;Bae et al, 2005). For a complete listing of all raw array data for both cyclopamine and DAPT treatments plus an expanded table showing P values for fold changes under both conditions, see Supplemental Tables 3-12.…”
Section: Cyclopamine and Dapt Treatmentsmentioning
confidence: 99%
“…This early myogenic commitment and allocation to the slow-twitch lineage is directed by members of the Hh family of secreted glycoproteins that are expressed by axial midline tissues [5][6][7] . Loss of Hh signaling, caused by mutational inactivation of genes encoding Sonic hedgehog (Shh) or the Hhtransducing protein Smoothened (Smo), impairs the development of some or all cells of the slow muscle lineage 8,9 , as shown by the loss of expression of the slow myosin heavy chain (MyHC) isoform and the homeodomain protein Prox1markers that are exclusively expressed by slow-twitch fibers 2,10 . Conversely, ectopic Hh activity is sufficient Using PCR, we assembled a full-length cDNA clone corresponding to zebrafish ubo and analyzed its expression pattern during embryonic development by whole-mount in situ hybridization.…”
mentioning
confidence: 99%